The influence of mean stress in the design of bridges with HFMI-treated welds - Investigation of design models to the Eurocode - Nilsson, Johan (My University, 2020)
ABSTRACT High-frequency mechanical impact (HFMI) is a post-weld treatment method to increase the fatigue strength of welded components. Most of the research on the performance of HFMI-treated joints has been carried out on structures subjected to constant amplitude loading. However, traffic loads on bridges can generate high and varying mean stresses, which are effects that are not covered by any design recommendations based on these earlier researches. A recent published report suggests a design framework that allows bridge designers to include the effect of mean stress under variable amplitude loading, without information about the stress range spectrum. In this work, traffic simulations are performed to investigate the validity of the suggested design framework, showing that the same results are obtained even for an increased traffic data pool. The same simulations are carried out on Dutch traffic, revealing that the design framework is applicable to traffic situations in other countries than Sweden. Finally, an alternative design framework is developed and presented.
Keywords: fatigue; bridge; HFMI; variable amplitude; mean stress; design